The Influence of Human Relations and Physical Environmental Conditions on Employee Performance Through Work Ethic at The Department of Cooperations in The City of Binjai - Yusra Faisal, Ahmad; B, Mesra (CV. Lafadz Jaya, 2023)
The purpose of this study was to determine and analyze the influence of human relations and physical environmental conditions on employee performance mediated by work ethic at the Binjai City Cooperative Office. This research was carried out at the Binjai City Cooperative Office. The type of research is associative quantitative. The population in this study was 50 employees with ASN and honorary status at the Binjai City Cooperative Service Office. The sampling technique in this research uses a saturated sample where the entire population is sampled. The results of this study indicate that Human Relations has a significant influence on employee performance with a T statistic > 1.96 and a P value <0.05. However, the physical condition of the environment does not have a significant influence on employee performance because the T statistic value is < 1.96 and the P value is > 0.05. Work ethic is proven to have a significant influence on employee performance, where increasing work ethic is related to increasing employee performance. Furthermore, mediation analysis shows that work ethics do not have a mediating effect in the relationship between Human Relations and employee performance, as well as between physical environmental conditions and employee performance. These results indicate that although there is a relationship between these factors, the role of work ethics in bridging their influence on employee performance is not observed. These findings provide important insights for organizational management in understanding the factors that influence employee performance. This research also contributes to the understanding of the mediating mechanisms of work ethic in the context of the relationship between certain factors and employee performance. Even though the physical condition of the environment does not have a significant impact, this research emphasizes the importance of maintaining and improving Human Relations and fostering a positive work ethic in order to improve employee performance within the Binjai City Cooperative Office.